2001
DOI: 10.1002/bit.1120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crown ethers on structure, stability, activity, and enantioselectivity of subtilisin Carlsberg in organic solvents

Abstract: Colyophilization or codrying of subtilisin Carlsberg with the crown ethers 18-crown-6, 15-crown-5, and 12-crown-4 substantially improved enzyme activity in THF, acetonitrile, and 1,4-dioxane in the transesterification reactions of N-acetyl-L-phenylalanine ethylester and 1-propanol and that of (±)-1-phenylethanol and vinylbutyrate. The acceleration of the initial rate, V 0 , ranged from less than 10-fold to more than 100-fold. All crown ethers activated subtilisin substantially, which excludes a specific macroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 61 publications
4
15
0
Order By: Relevance
“…In fact, several applications in industry have been used to generate kilograms of product in this fashion [10]. Instinctively, one might assume that proteins would be denatured in organic solvents; however, experimental characterization, though limited, has suggested that this is not the case [12,13]. Furthermore, the ultimate test for structural fidelity with proteins is generally considered to be functionality, which can obviously be retained and utilized in organic media.…”
Section: Nonaqueous Environmentsmentioning
confidence: 99%
“…In fact, several applications in industry have been used to generate kilograms of product in this fashion [10]. Instinctively, one might assume that proteins would be denatured in organic solvents; however, experimental characterization, though limited, has suggested that this is not the case [12,13]. Furthermore, the ultimate test for structural fidelity with proteins is generally considered to be functionality, which can obviously be retained and utilized in organic media.…”
Section: Nonaqueous Environmentsmentioning
confidence: 99%
“…There have been a number of studies focusing on increasing the activity of enzymes suspended in organic solvents, for example by controlling the pH-value of the solution from which the enzyme is prepared (Carrea and Riva, 2000;Costantino et al, 1997;Gupta, 2000;Klibanov, 1986;Yang et al, 1993;Zaks and Klibanov, 1985); enzyme lyophilization in the presence of lyoprotectants (various sugars) (Belton and Gil, 1994;Carpenter and Crowe, 1989;Dabulis and Klibanov, 1993;Griebenow and Klibanov, 1997), salts (Khmelnitski et al, 1994;Ru et al, 2000;Sasaki and Kise, 1999), crown ethers (Bross et al, 1995;Griebenow et al, 2001;Reinhoudt et al, 1989;Santos et al, 2001;Van Unen et al, 1998, cyclodextrins (Griebenow et al, 1999a;Montañez et al, 2002;Ooe et al, 1999;Santos et al, 1999), ligands (imprinting with substrates and substrates analogs) (Russell and Klibanov, 1998), crown ether modified peptides (Tremblay et al, 2005); employing cross-linking enzymes crystals (CLECs) (Triantafyllou et al, 1997;Wang et al, 1997); immobilization (Kwon et al, 1999;Suzawa et al, 1995), and hydrophobic ion-pairing (Kendrick et al, 1997;Meyer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been focused on strategies to overcome this issue, including enzyme immobilization on porous and non-porous solid supports 12,13 , chemical modification of the enzymes' surfaces to improve compatibility with solvents 14 , protein engineering 2 , and enzyme co-lyophilization with different types of excipients, such as cyclodextrins 10,15 , crown ethers [15][16][17] , and inorganic salts [18][19][20] . Specifically, the co-lyophilization of enzymes with inorganic salts from aqueous solution, termed salt activation, has been remarkably successful.…”
Section: Introductionmentioning
confidence: 99%